2012
DOI: 10.1039/c2ob07015d
|View full text |Cite
|
Sign up to set email alerts
|

A simple synthesis of N-perfluoroacylated and N-acylated glycals of neuraminic acid with a cyclic aminic substituent at the 4α position as possible inhibitors of sialidases

Abstract: A simple protocol for the synthesis of N-perfluoroacylated and N-acylated glycals of neuraminic acid, with a secondary cyclic amine (morpholine or piperidine) at the 4α position, has been set-up, starting from peracetylated N-acetylneuraminic acid methyl ester that undergoes, sequentially to its direct N-transacylation followed by a C-4 amination, a β-elimination, and a selective hydrolysis of the ester functions, without affecting the sensitive perfluorinated amide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Preparation of 2,6-anhydro-5-acetamido-3,5-dideoxy-D-glycero-D-talo-non-2-enoic acid (7a). Starting from protected glycal 9a 13,14 (66 mg, 0.14 mmol), according to the general two step procedure Zemplén reaction followed by selective hydrolytic method A, glycal 7a was obtained (31 mg, 75%), as a white solid, showing: [α] 23 D , −98.9 (c 1 in MeOH); δH (CD 3 OD) 6.02 (1H, d, J 3,4 5.0 Hz, 3-H), 4. 27-4.14 (3H, overlapping, 4-H, 6-H and 5-H), 3.92 (1H, ddd, J 8,9a 2.3, J 8,9b 5.3, J 8,7 9.2 Hz, 8-H), 3.83 (1H, dd, J 9a,8 2.3, J 9a,9b 11.4 Hz, 9a-H), 3.67 (1H, dd, J 9b,8 5.3, J 9b,9a 11.4 Hz, Preparation of 2,6-anhydro-5-(2,2,2-trifluoroacetamido)-3,5dideoxy-D-glycero-D-talo-non-2-enoic acid (7b).…”
Section: Preparation Of N-perfluoracyl Glycals 2c D and 7a-dmentioning
confidence: 99%
“…Preparation of 2,6-anhydro-5-acetamido-3,5-dideoxy-D-glycero-D-talo-non-2-enoic acid (7a). Starting from protected glycal 9a 13,14 (66 mg, 0.14 mmol), according to the general two step procedure Zemplén reaction followed by selective hydrolytic method A, glycal 7a was obtained (31 mg, 75%), as a white solid, showing: [α] 23 D , −98.9 (c 1 in MeOH); δH (CD 3 OD) 6.02 (1H, d, J 3,4 5.0 Hz, 3-H), 4. 27-4.14 (3H, overlapping, 4-H, 6-H and 5-H), 3.92 (1H, ddd, J 8,9a 2.3, J 8,9b 5.3, J 8,7 9.2 Hz, 8-H), 3.83 (1H, dd, J 9a,8 2.3, J 9a,9b 11.4 Hz, 9a-H), 3.67 (1H, dd, J 9b,8 5.3, J 9b,9a 11.4 Hz, Preparation of 2,6-anhydro-5-(2,2,2-trifluoroacetamido)-3,5dideoxy-D-glycero-D-talo-non-2-enoic acid (7b).…”
Section: Preparation Of N-perfluoracyl Glycals 2c D and 7a-dmentioning
confidence: 99%
“…Indeed, some 2-unsaturated congeners (glycals) of Neu5Ac have shown important inhibitory activity against various bacterial and viral sialidases (neuraminidases, NA), enzymes involved in the spreading of influenza infection. [11] Continuing our interest in the chemistry of Neu5Ac and NA inhibitors, [12][13][14][15][16][17][18] we herein report a simple procedure to access 4β-acylaminoglycals sharing the structure of compounds 3a and 3b, chosen as models in the synthetic protocol. [11] Continuing our interest in the chemistry of Neu5Ac and NA inhibitors, [12][13][14][15][16][17][18] we herein report a simple procedure to access 4β-acylaminoglycals sharing the structure of compounds 3a and 3b, chosen as models in the synthetic protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, differently to the well-established oxazoline chemistry, 18 it was reported that the acidic treatment of the oxazoline 3a afforded the 4-epi hydroxyl derivative 4b, as a single product, in variable yields (42-88%), calling for further studies. 6,[9][10][11][12][13] As a result of our continuing interest in the sialic acid chemistry/ biochemistry, 2,3,7,[14][15][16][19][20][21][22][23] in this work we solved this mechanistic puzzle, as we unveil that, the acidic hydrolysis of the 4,5-oxazoline 3a affords the amino ester 5, which could be isolated in good yields and fully characterized under appropriate work-up conditions. Furthermore, we detailed the shortened synthesis of the precursor of BCX 2798 (2c) and other sialidase inhibitors (such as BCX 2755 and various C4 triazole derivatives) further highlighting the synthetic utility of 5.…”
mentioning
confidence: 92%
“…8,14 In this context, our group has revealed the conditions to perform a critical intermolecular nucleophilic attack on 3a at its C4 position, while avoiding its intramolecular formation, and reported the synthesis of several C5-peruorinated 4-epi DANA derivatives. 2,3,7,15,16 Overall, the synthetic strategies involving the synthon 3a could be summarized with three distinctive reactions (Scheme 1): (a) a nucleophilic attackvia S N 2on the carbon at C4, which eventually opens up the oxazoline ring, thus restoring the acetyl group at C5 (analogously to the reaction used for the insertion of the azido group at C4), 17 (b) a hydrolytic ring-opening caused by the direct attack of a water molecule on the sp 2 -carbon of the oxazoline ring, which affords the 4b-hydroxy derivative 4b, 6,[9][10][11][12][13] and (c) a nucleophilic attack on the anomeric carbon (C2), followed by a shi of the double bond and the restoration of the N-acetyl group through a Ferrier reaction. 8,14 To date, the formation of the amino ester 5, an isomer of 4b and derived from the C]N bond cleavage of the oxazoline ring, has never been described.…”
mentioning
confidence: 99%